Adolescents' reports of parental socio-economic status - Are they really valid? - I Perera; L Ekanayake (College of Community Physicians of Sri Lanka, 2011)
Objective: To assess whether adolescents could be relied on as proxies to provide accurate information about their parental socio-economic status. Methodology: A descriptive cross-sectional study was conducted among 1225, 15-year-olds selected from 42 schools in the Colombo district using a stratified cluster sampling technique. Data were collected by means of self-administered questionnaires to both adolescents and their parents. Results: Response rates of adolescents regarding their parents' occupation status were very high. The strength of agreement between parental and adolescents reports was assessed using the Kappa statistic. The respective kappa statistics (95% CI) were 0.84 (0.82-0.86) for fathers occupation and 0.85 (0.82- 0.88) for mother's occupation. Conclusion: the results indicated that 15-year-old adolescents could be considered as proxies to provide accurate information about their parents' occupational status. Key words: occupation; questionnaires; Kappa statistic; adolescents DOI: 10.4038/jccpsl.v14i1.2942 Journal of the College of Community Physicians of Sri Lanka Vol.14(1) 2009 9-13